2017
DOI: 10.1371/journal.pone.0181072
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Staphylococcus aureus in a burn unit of a tertiary care center in Ghana

Abstract: BackgroundIn developing countries, hospitalized burn victims are at high risk of nosocomial infections caused by Staphylococcus aureus. Risk factors include poor infection control practices, prolonged hospitalisation and limited capacity for laboratory microbiological analyses. These problems are compounded by widespread use of antibiotics that drives the spread of multi-drug resistant bacteria.MethodsDuring the study period (November 2014-June 2015), nasal and invasive S. aureus isolates were collected consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 46 publications
7
33
2
Order By: Relevance
“…Limited evidence from Nigeria, Ghana, and Malawi suggests that bacterial antibiotic resistance is common among burn wound cultures. [2124] Several evaluations of burn wound microbiology in middle or low-income countries outside of this region have demonstrated similar findings. [25–33] However from the published literature, the relationship between burn wound colonization with MDR bacteria and patient outcomes in LMICs is unclear.…”
Section: Discussionmentioning
confidence: 69%
“…Limited evidence from Nigeria, Ghana, and Malawi suggests that bacterial antibiotic resistance is common among burn wound cultures. [2124] Several evaluations of burn wound microbiology in middle or low-income countries outside of this region have demonstrated similar findings. [25–33] However from the published literature, the relationship between burn wound colonization with MDR bacteria and patient outcomes in LMICs is unclear.…”
Section: Discussionmentioning
confidence: 69%
“…The overall prevalence of S. aureus infection of burn wounds was 80% with majority of the isolates being MRSA. This is much higher than previously reported in tertiary care health care facilities of Ethiopia [31] and Ghana [32]. Bed sores are more strongly associated with prolonged hospital stays [33].…”
Section: Discussionmentioning
confidence: 65%
“…In Ghana, Saba et al (2017) isolated MRSA (17%) from handles and other points of contact in a public hospital environment. In the Burn Center of Korle Bu Teaching Hospital in Ghana, 50% of patients were infected with S. aureus including MRSA (Amissah et al, 2017). In Côte d'Ivoire, previous studies have reported the occurrence of S. aureus strains harboring PVL gene.…”
Section: Staphylococcusmentioning
confidence: 99%
“…In other sub-Saharan Africa countries, the frequency of PVL-positive S. aureus in clinical samples is high. In Ghana, PVL-encoding genes were detected in 75% (42/56) of S. aureus blood culture (Dekker et al, 2016) and in 27% (17/62) of carriage of PVL-positive S. aureus in burn patients (Amissah et al, 2017). This gene carriage rate was higher (90.7%; 68/75) in communityacquired-S. aureus isolated in Mozambique (van der Meeren et al, 2014), in the Democratic Republic of the Congo (49.1%) (Vandendriessche et al, 2017) and in Nigeria (33.3%; 17/51) in clinical infections (Shittu et al, 2012).…”
Section: Antibiotic Profilesmentioning
confidence: 99%